2019
DOI: 10.3847/1538-4357/ab3d37
|View full text |Cite
|
Sign up to set email alerts
|

ALMA Monitoring of Millimeter Line Variation in IRC +10216. I. Overview of Millimeter Variability

Abstract: Temporal variation of millimeter lines is a new direction of research for evolved stars. It has the potential to probe the dynamical wind launching processes from time dimension. We report here the first ALMA (Atacama Large Millimeter Array) results that cover 817 days of an on-going monitoring of 1.1 mm lines in the archetypal carbon star IRC +10216. The monitoring is done with the compact 7-m array (ACA) and in infrared with a 1.25 m telescope in Crimea. A high sensitivity of the cumulative spectra covering … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…For example, IRC+10216 has been examined in great detail (eg. Dinh-V-Trung & Lim 2008; Tenenbaum et al 2010;Chau et al 2012;He et al 2019). These studies show that C-stars in particular have a rich chemistry which gives rise to multiple spectral signatures at radio wavelengths.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…For example, IRC+10216 has been examined in great detail (eg. Dinh-V-Trung & Lim 2008; Tenenbaum et al 2010;Chau et al 2012;He et al 2019). These studies show that C-stars in particular have a rich chemistry which gives rise to multiple spectral signatures at radio wavelengths.…”
Section: Introductionmentioning
confidence: 94%
“…In depth spectral studies of AGB stars are sparse at 43 GHz as most molecular surveys are conducted at mm wavelengths (e.g. Bujarrabal et al 1994;Decin et al 2018;He et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…28, and references therein]. The shocks and changes in luminosity created by these pulsations sculpt the inner outflow in a number of ways: the high densities associated with the shocks drive dust formation, while the intense radiation field near maximum light destroys some of the closest dust [e.g 28]; energy from shocks ionises a substantial fraction of material in the inner envelope, leading to free-free emission from the radio photosphere, while also fuelling a number of chemical pathways [29,30]; and the changes in luminosity lead to large changes in the pumping of high-excitation lines and hence the energy balance of the circumstellar gas [31,32].…”
Section: Mass-loss Historiesmentioning
confidence: 99%
“…Complementary to the continuum, recent studies have found significant variability in sub-mm lines, particularly those with high excitation temperatures [e.g. 31,32]. The variability of some of these lines correlates strongly with the changes in luminosity (probed by the near-IR), while others are strongly anti-correlated.…”
Section: Mass-loss Historiesmentioning
confidence: 99%
“…In some cases, these spectral indices are measured within a band (Pérez et al 2020;Lee et al 2020), which minimizes time-variability in the flux calibration but may introduce other uncertainties. The flux calibration also affects results from programs that require accurate monitoring with time (e.g He et al 2019;Cleeves et al 2017), ratios of emission lines in different bands (e.g. Flaherty et al 2018;Matrà et al 2017), or comparison of fluxes from different objects in a survey (e.g Tobin et al 2020;Ansdell et al 2016).…”
Section: Introductionmentioning
confidence: 99%